Endovascular procedures and nursing care: managing vascular access wounds - Dziekiewicz, Anna; Bystron, Joanna; Kobiałka, Jakub; Ludwig, Bartłomiej (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2023)
The common femoral artery (CFA) is frequently utilized access site for endovascular procedures, but this approach can lead to several complications, including haematomas, pseudoaneurysms, bleeding at the access site, and surgical site infections (SSI). Although appropriate management of vascular access wounds can minimize the risk of complications, SSI is still a significant concern for patients undergoing endovascular procedures. Therefore, nursing personnel must possess comprehensive knowledge of the techniques used to access CFA, potential complications, and the nursing care required to manage them effectively. Nurses play a critical role in preventing complications associated with endovascular procedures, as they can identify patients with a high risk of complications. With appropriate education, nurses can inform patients about the measures that can be taken to reduce the risk of adverse events. Regular assessment and monitoring of the wound are essential for the early detection of complications and the implementation of measures to minimize their negative effects.